2010
DOI: 10.3390/sym2010112
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Symmetry Breaking Phenomenon Caused by a Phase Transition

Abstract: Abstract:We report the mechanism and scope of "preferential enrichment", which is an unusual symmetry-breaking enantiomeric resolution phenomenon that is initiated by the solvent-assisted solid-to-solid transformation of a metastable polymorphic form into a thermodynamically stable one during crystallization from the supersaturated solution of certain kinds of racemic mixed crystals (i.e., solid solutions or pseudoracemates) composed of two enantiomers. The mechanism can well be interpreted in terms of a symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 46 publications
2
45
2
Order By: Relevance
“…In contrast, CPPPA·INA showed an excellent enantiomeric enrichmentupto9 3% ee in the motherliquor by repeating recrystallization startingf rom the supersaturated 2-PrOH solution of (RS)-CPPPA·INA ( Figure 6). However,t he behaviour of this PE phenomenon was different from that reported for the first generation of organic salts ( Figure S2) [8][9][10][11][12] and the cocrystal of DL-phenylalanine( Phe) [13] or DL-arginine (Arg) [14] with fumaric acid. Namely,f or CPPPA·INA, 1) the space group of the (RS)- Chem.…”
Section: Mechanism Of Pe For Cpppaand Cpppa·inacontrasting
confidence: 72%
See 2 more Smart Citations
“…In contrast, CPPPA·INA showed an excellent enantiomeric enrichmentupto9 3% ee in the motherliquor by repeating recrystallization startingf rom the supersaturated 2-PrOH solution of (RS)-CPPPA·INA ( Figure 6). However,t he behaviour of this PE phenomenon was different from that reported for the first generation of organic salts ( Figure S2) [8][9][10][11][12] and the cocrystal of DL-phenylalanine( Phe) [13] or DL-arginine (Arg) [14] with fumaric acid. Namely,f or CPPPA·INA, 1) the space group of the (RS)- Chem.…”
Section: Mechanism Of Pe For Cpppaand Cpppa·inacontrasting
confidence: 72%
“…[5] Meanwhile,p referentiale nrichment (PE), reportedb yu si n 1996,i sat otally opposite phenomenon to PC;i nP E, the spontaneous enantiomeric resolution wasf ound to occur without any chiral seed crystals uniquely for ac ertain kind of mixed crystals(i.e.,solid solutions) composed of arandom to fairly ordered arrangemento ft wo enantiomers at the definedp osition in the crystal lattice (Figures S1 ba nd S1 c). [6][7][8][9][10][11][12] Consistent with the proposed mechanism of PE with respectt ot he first generation of organic salts (FiguresS1c and S2), there are five mandatoryrequirements forthe occurrence of PE:#1) sufficient solubilityd ifference (pure enantiomer @ racemate;m ore than twice), #2) occurrenceo fasolvent-assisted solid-to-solid polymorphict ransition during crystallization, #3) formation of uniquec rystal structures involving heterochiralc yclic RS dimer chainsa sw ell as homochiral1 DR and S chains at the end of the polymorphic transition, #4) selective redissolutiono ft he excess one enantiomer from the transformedd isordered crystals into the motherl iquor, and# 5) eventual deposition of stablen onracemic mixed crystals capable of memorizing the evento fc hiral symmetry breaking. [6][7][8][9][10][11][12] Recently,i th as been reported that cocrystallization of several amino acids with achirald icarboxylica cids can induce a good to excellent PE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 In this article, we report an example of advantageous use of polymorphic transformation, i.e., an unusual symmetry-breaking enantiomeric resolution phenomenon that is initiated by the solvent-assisted solid-to-solid polymorphic transition during crystallization from the supersaturated solution of a certain kind of racemic crystals. [11][12][13] Exploitation of economically and environmentally acceptable enantiomeric resolution methods have long been the subject of considerable interest in connection with the rationalization of the origin of biomolecular homochirality on Earth [14][15][16][17][18][19][20] as well as the industrial and pharmaceutical needs for chiral organic substances. [21][22][23][24][25] Among them, the methods for enantiomeric resolution of racemates by crystallization are classified into two categories; 26 one is a straightforward method to separate enantiomers in the absence of an external chiral element and the other is an indirect method using an external chiral element, such as a diastereomeric salt formation followed by fractional crystallization 22,[27][28][29] or a diastereoselective host-guest inclusion complexation (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The stochastic nature was nicely demonstrated in the crystallization of sodium chlorate [25] and amino acids glutamic acid and lysine [26]. Relevant results have been reviewed from several different aspects [27][28][29][30][31][32] and extended to phase transitions in general [33][34].…”
Section: Stochastic Experimental Observations Relevant For Chirality mentioning
confidence: 99%